Аналіз реологічних властивостей різновидів майонезу - Бухкало, Світлана Іванівна; Іглін, Сергій Петрович; Ольховська, Вікторія Олегівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
У матеріалах статті розглянуті можливості визначення реологічних властивостей для технологічних процесів виробництва майонезу. Розробки проведені з метою вибору сучасних високоефективних науково-обгрунтованих технологій: 1) різновидів технології та їх закономірностей з урахуванням специфічних особливостей компонентів; 2) на різних стадіях проектування і обґрунтування моделей устаткування. Представлені приклади і деякі особливості можливих рішень, які засновані на експериментальних даних розробки механізмів процесів і їх наукового обґрунтування у вигляді об'єктів технології. Проблеми технології майонезів розглядається у вигляді складних комплексних процесів, їх досліджень, аналізу енерго- і ресурсозберігаючих складових. Проаналізовано умови застосування реологічних властивостей та їх параметри, сформовано рекомендації для вибору реологічної моделі конкретного неньютонівського середовища.

The materials presented of innovative development opportunities determination of rheological properties for technological processes of mayonnaise production. The developments have been carried out with the aim of selecting modern highly efficient science-based technologies: 1) types of technology and their regularities, taking into account specific features of the components; 2) at different stages of design and justification of equipment models. Examples and some features of possible solutions are presented, which are based on experimental data of the development of process mechanisms and their scientific substantiation in the form of objects of technology. The materials are devoted to the results of researches of properties of technical and technological innovations of modern systems as object studies the possibility of complex properties in the development system increasing the economic efficiency of new sources. A review of the literature and the necessary articles written on the subject: as technologies and develop and become more complex, energy needs increase greatly; types and evidence-based methods of new material resource, as well as the possibility of calculating the basic set of main indicators are classified; identified possible areas of work in obtaining the necessary results. The conditions of application of rheological models and their parameters are analyzed, recommendations in relation to the selection of model for a particular non-Newtonian fluid are formed.
Analysis rheological properties of mayonnaise mass
Keywords: специфічні особливості виробництва; scientifically sound methods